(untitled) (International Journal of Engineering and Computer Science, 2025)
In the rapidly evolving landscape of cybersecurity, organizations are increasingly vulnerable to two prominent forms of attacks: Distributed Denial of Service (DDoS) and Social Engineering. These attack vectors, while distinct in execution, share a common goal—disrupting the confidentiality, integrity, or availability of systems and data. This paper provides an in-depth exploration of both threats by examining their methodologies, real-world applications, and the socio-technical implications they present in digital infrastructure. Social Engineering exploits the psychological tendencies of individuals, manipulating human behavior to bypass technical safeguards. Attackers leverage deception, persuasion, and trust-building techniques to extract sensitive information or gain unauthorized access. The prevalence of phishing, pretexting, and reverse social engineering showcases how easily human error can be weaponized, particularly in environments lacking sufficient awareness and training. On the other hand, DDoS attacks target the availability of online services by overwhelming network resources through massive volumes of malicious traffic. These attacks often utilize botnets—networks of compromised devices—to execute large-scale, coordinated disruptions that can take down websites, cripple digital services, and result in significant financial losses. Modern variants such as SYN floods and HTTP request attacks have made mitigation increasingly complex, particularly when combined with emerging attack automation tools. This paper synthesizes key academic insights, presents real-world incidents, and reviews existing prevention mechanisms including behavior-based detection, protocol refinement, black hole routing, and user education. Furthermore, it compares the psychological versus technical nature of both attack types, emphasizing the need for a hybrid approach to defense—integrating human-centric training with technological countermeasures. Ultimately, the study underscores that cybersecurity is no longer a purely technical domain. It requires a multidisciplinary response strategy that aligns behavioral awareness with resilient infrastructure design. Only through such integrative efforts can the growing threat of DDoS and Social Engineering be effectively mitigated.